A mineração de areia industrial na Região Sul do Brasil - Ferreira, Gilda Carneiro [UNESP]; Daitx, Elias Carneiro [UNESP] (Escola de Minas, 2003)
In the south of Brazil, ten mining companies produce industrial sand by processing quartzite sand composed of quartz and sandstone. Granulometric and mineralogical methods are used which enhance the value of these minerals. The State of Santa Catarina is the largest producer of industrial sand in the southern region, where they mine coast sediments from Quaternary. Most production is in the Araguari area. The state boasts the largest foundry in Latin América, located in Joinville. Campo Largo, State of Parana, and Viamão, State of Rio Grande do Sul, are primary suppliers for the ceramic and glass industries. This significant consumer market has attracted the attention of the country's largest industrial sand mining company, with mineral areas in the State of São Paulo, which is considering alternative installation of new mines in Paraná and Santa Catarina States.

Na Região Sul do Brasil existem atualmente dez empresas de mineração produzindo areia industrial a partir do beneficiamento de areia quartzosa, de quartzito e de arenito, utilizando processos de seleção granulométrica e mineralógica e agregando valor a esses bens minerais. O Estado de Santa Catarina é o maior produtor de areia industrial da Região Sul, com destaque para a região de Araquari, onde são lavrados sedimentos quaternários litorâneos, abastecendo principalmente a maior fundição da América Latina, localizada em Joinville. As minas situadas nos Estados do Paraná, em Campo Largo, e do Rio Grande do Sul, em Viamão, abastecem com prioridade as indústrias de cerâmica e de vidro, respectivamente. Esse expressivo mercado consumidor tem atraído a atenção da maior mineradora de areia industrial do país, com jazidas situadas em São Paulo, a qual tem buscado alternativas para a instalação de novas minas nos Estados do Paraná e de Santa Catarina.
Keywords: industrial sand; mining; producer market; areia industrial; mineração; mercado produtor